Morphological Identification and Diversity Analysis of Fossil Diatoms from Diatomite Sangiran Central Java Indonesia - Khustina, Yenny Chusna; Solihin, Dedy Duryadi; Pratiwi, Niken TM (Perhimpunan Biologi Indonesia, 2014)
Diatomite Sangiran is diatom fossil rich sediment. The aim of this research was to study the diversity of fossildiatoms from Sangiran, Indonesia based on morphological characteristics. Samples were taken from lower, middle,and upper sediment layers based on their different physical features with three replications each. Diatomiteextraction was performed following modification of Setty (1966) and frustule counting was accomplished by censusmethod. There were total 50 species found in diatomite layers. The diversity analysis showed that highest speciesrichness (21-22), diversity (1.35-1.47), and evenness index (0.44-0.48) were belong to the lower layer. The highestfrustule abundance (9.66x107-1.43x108 frustules/gram) and dominance index (0.67-0.72) were belong to themiddle layer. On the other hand, highest centrales:pennales ratios (0.73-1.11) were belong to the upper layer. Thesediment layers signified an obvious indication of gradual changes from marine to freshwater environment.Dendrogram analysis using MINITAB.v.15.1.2 software denoted similarity between lower sediment layer and theyounger layers was 72.12%; while similarity between middle and upper layers 92.63%.Keywords: diatom, diatomite, diversity, morphology, Sangiran